Wilhelmgümbelite, [ZnFe2+Fe3+3(PO4)3(OH)4(H2O)5]·2H2O, a new schoonerite-related mineral from the Hagendorf Süd pegmatite, Bavaria. (1st April 2017) - Grey, I. E.; Keck, E.; Kampf, A. R.; Macrae, C. M.; Glenn, A. M.; Price, J. R.
Wilhelmgümbelite, ideally [ZnFe2+Fe3+3(PO4)3(OH)4(H2O)5]·2H2O, is a new secondary phosphate mineral related closely to schoonerite, [ZnMnFe2+2Fe3+(PO4)3(OH)2(H2O)7]·2H2O, from oxidized zones of the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Wilhelmgümbelite occurs as radiating sprays of needle-like rectangular laths, up to 0.2 mm long and with colour varying from light yellow brown to orange red. Cleavage is perfect parallel to {010}. The mineral is associated closely with an oxidized pseudomorph of phosphophyllite, recently named steinmetzite. Other associated minerals are albite, apatite, chalcophanite, jahnsite, mitridatite, muscovite and quartz. The calculated density of wilhelmgümbelite is 2.82 g cm–3. It is optically biaxial (+) with α = 1.560(2), β = 1.669(2), γ = 1.718(2), 2V(meas) = 63(1)° and 2V(calc.) = 65°. Dispersion is weak with r > v, orientation X = b, Y = c, Z = a. Pleochroism is weak, with colours Z = orange brown, Y = yellow brown, X = light yellow brown, Z >> Y > X. Electron microprobe analyses (average of seven analyses, seven crystals) with H2O and FeO/Fe2O3 calculated on structural grounds, gave FeO 5.8, Fe2O3 25.0, MnO 2.6, ZnO 16.4, P2O5 28.7, H2O 23.4, total 101.9 wt.%. The empirical formula, scaled to 3 P and OH– adjusted for charge balance is Zn1.50Mn2+0.27Fe2+0.60Fe 3+2. 33(PO4)3·(OH)2.73(H2O)8.27. The structural formula is [Zn(Mn0.27Fe3+0.73)∑1.0(Zn0.25Fe2+0.15Fe3+0.60)∑1.0(Zn0.25Fe2+0.45)∑0.7Fe3+(PO4)3(OH, H2O)9]·2H2O. Wilhelmgümbelite has orthorhombic symmetry, Pmab, Z = 4, with the unit-cell parameters of a = 10.987(7) Å, b = 25.378(13) Å, c = 6.387(6) Å and V = 1781(2) Å3. The strongest lines in the powder X-ray diffraction pattern are [dobs in Å(Iobs) (hkl)] 12.65 (100) (020); 8.339 (5) (120); 6.421 (14) (001); 6.228 (8) (011); 4.223 (30) (120) and 2.111 (7) (0 12 0). Wilhelmgümbelite is an oxidized form of schoonerite, with the Mn2+ replaced principally by Fe3+. Its structure differs from that of schoonerite in having the Zn partitioned between two different sites, one five-coordinated as in schoonerite and the other tetrahedrally coordinated. Wilhelmgümbelite also differs structurally from schoonerite in having partial occupation of one of the Fe sites, which appears to be correlated with the Zn partitioning.